Warm tropics / Muhammad Faiz Bin Mohd Ariffin - Mohd Ariffin, Muhammad Faiz (Mohd Ariffin, 2022)
The inspiration of my artwork is to maintain a contemporary design at the same time encourage the use of natural dye in the making of batik to ensure that the life cycle of the environment is not polluted. I tried to use natural dye coloring from original plant extracts such as leaves and fruit. I really like natural dye because it saves money and can avoid environmental pollution. I also believe that by using this method, we get goodness and pleasure because it is not easy to produce natural dye coloring because the process is very challenging. However, the results of these colourings are beautiful and the hues are calming and harmonious. This is what I try to reflect in my artworks, a harmonious design in calming colours.